1997
DOI: 10.1128/jb.179.9.2987-2993.1997
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a glucose-repressed pyruvate kinase (Pyk2p) in Saccharomyces cerevisiae that is catalytically insensitive to fructose-1,6-bisphosphate

Abstract: We have characterized the gene YOR347c of Saccharomyces cerevisiae and shown that it encodes a second functional pyruvate kinase isoenzyme, Pyk2p. Overexpression of the YOR347c/PYK2 gene on a multicopy vector restored growth on glucose of a yeast pyruvate kinase 1 (pyk1) mutant strain and could completely substitute for the PYK1-encoded enzymatic activity. PYK2 gene expression is subject to glucose repression. A pyk2 deletion mutant had no obvious growth phenotypes under various conditions, but the growth defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 51 publications
(45 reference statements)
2
93
2
Order By: Relevance
“…We hope that future studies by us and others can provide additional support for the hypothesis put forward in this work. Notably, there is indication that flux-sensing mechanisms might also be present in other organisms: recently, it was reported that the budding yeast Saccharomyces cerevisiae shows a similar relationship between the glycolytic flux and FBP (7,38) and also its pyruvate kinase is feedforward activated by FBP (39). Thus, our findings are likely relevant also for other organisms.…”
Section: Discussionsupporting
confidence: 52%
“…We hope that future studies by us and others can provide additional support for the hypothesis put forward in this work. Notably, there is indication that flux-sensing mechanisms might also be present in other organisms: recently, it was reported that the budding yeast Saccharomyces cerevisiae shows a similar relationship between the glycolytic flux and FBP (7,38) and also its pyruvate kinase is feedforward activated by FBP (39). Thus, our findings are likely relevant also for other organisms.…”
Section: Discussionsupporting
confidence: 52%
“…With the completion of the yeast genome sequencing project, an open reading frame coding for a protein with high homology to Pyk1 has been reported. The characterization of this gene indicated the existence of a Pyk2 protein, which is insensitive to FBP and whose expression is repressed by glucose (17). In this work we identify both Pyk1 and Pyk2 as in vitro and in vivo substrates of PKA, characterize their behavior as PKA substrates, and present a preliminary study of the effect of phosphorylation on the kinetics of pyruvate kinase.…”
mentioning
confidence: 89%
“…The decrease in specific activity correlated with the levels of Pyk1 followed by Western blot. According to these results the kinetic experiments that follow were performed on partially purified preparations of Pyk from cells in a pre-diauxic shift stage, in which the specific activity of Pyk1 is maximal and there is no expression of Pyk2 (17).…”
Section: Kinetic Constants For Pyk1 and Pyk2mentioning
confidence: 99%
“…Yeast defective in this gene fail to grow on glucose, but they can grow on ethanol or other gluconeogenic carbon sources (37). Boles et al (37) discovered the existence of an isoform of PK, Pyk2p, which they reported "is subject to glucose repression and. .…”
Section: Examination Ofmentioning
confidence: 99%